(untitled) (Pravaha, 2021)
The field of Artificial Intelligence is enhancing rapidly which breakthroughs in image and speech recognition, autonomous robotics, language tasks, and game playing. AI is the part of human daily lives with knowing or unknowingly and there is no privacy because of social media and technology which is progressing rapidly from Sirito Tesla hands-free switch for highway and freeway self-driving car. The application AI in numerous ranges, from online services to business, education and healthcare. It is used mostly by organizations to advance their technique competences, automate resource-heavy tasks, and to make business forecasts based on big data rather than automatic means. Our routine transformed physical to virtual in banking, medical, education, marketing and others. It makes all process enhanced, faster, and supplementary perfect and has some extremely decisive functions too such as recognizing and foretelling fraudulent transactions, faster and credit scoring with automating manually intense data management practices. The fundamental goal of AI is to empower machines and computers to perform philosopher tasks for problem solving, decision making, awareness, and feeling human interaction. It is making inroads is self-learning solutions so it is gaining popularity due to its use of personalized learning, pace, and suggestions. Beyond innovative and powerful AI systems will be developed and deployed in the future, which could be transformative with negative as well as positive consequences also threats.